New Tendencies in Applying Music for Educational Purposes with Primary School Students - Yulia Poplavs’ka-Mel’nychenko (Pedagogical Discourse, 2012)
The article reveals the specifics in applying music for educational purposes at primary schools and proposes new tendencies in applying music as an active stimulator in the educational process involving primary school students.